Do alcohol policies affect everyone equally? An assessment of the effects of state policies on education-related patterns of alcohol use, 2011–2019. (1st October 2022) - Silver, Diana; Bae, Jin Yung; McNeill, Elizabeth; Macinko, James
Abstract: Background: Public policies are a powerful tool to change behaviors that may harm population health, but little is known about how state alcohol policies affect different population groups. This study assesses the effects of a comprehensive measure of the state alcohol regulatory environment (the State Alcohol Policy Score or SAPS) on heavy drinking—a risk factor for premature death—on different population groups, defined by levels of educational attainment, then by race/ethnicity, and sex. Methods: We pool each state's Behavioral Risk Factor Surveillance Survey (BRFSS) 2011–2019 and use robust Poisson regression analyses that control for individual-level factors, state-level factors (1 year lagged SAPS score for each state, state fixed effects), and year fixed effects to assess the relationship between SAPS and heavy drinking behaviors by education group. Interaction terms test whether education moderates the relationship by race/ethnicity and gender. Results: SAPS scores increased 2010–2018, but substantial gaps persist between states. A 10 % increase in a state's alcohol policy score is associated with a 2 % lower prevalence in current drinking (APR=0.97, 95 % CI=0.97–0.97, p < 0.0011) although not for those with a high school education or less. A 10 % increase in the SAPS was associated with a 3 % lower prevalence of heavy drinking; interaction terms in models reveal that a 10 % increase in the SAPS was associated with a lower prevalence of heavy drinking among those with less than a college education. Conclusion: Narrowing gaps in alcohol policies between states may reduce heavy drinking among those with lower educational attainment. Highlights: Higher state alcohol policy scores predict less heavy drinking for those with less education. Higher state scores predict more heavy drinking for those who completed college. Likelihood of heavy drinking in Whites w/o HS degree highest in low scoring states.